Factors Affecting Customer Interest in Buying Sharia Insurance Products (Study at PT. Asuransi Jasindo Syariah Medan Marketing Office) - Indira Rahayu; Alfi Amalia (TALENTA Publisher, Universitas Sumatera Utara, 2022)
This study was conducted with the aim of analyzing the factors that influence customer interest in buying sharia insurance products (Study at PT. Asuransi Jasindo Syariah Medan marketing office. A total of 65 respondents is the number of samples used in analyzing data using the T test, F test and R2 test The results of this study state that the factors that influence interest are promotion, product, price.The result is promotion, product, price simultaneously has a significant influence on interest in becoming a customer of PT.Assuransi Jasindo Syariah Medan Marketing Office. Â